Factors influencing the acquisition of corn seed in the State of Veracruz, Mexico - Vega-Bautista, María; Platas, Diego Esteban; Vilaboa-Arroniz, Julio; López, José Luis; Ortiz, Adriana Ivón; Neri, Martín (Revista de Ciencias Agrícolas, 2024)
Corn production is a fundamental agricultural activity in Mexico. However, producers face significant challenges in accessing improved seeds that can optimize yields. Identifying the factors influencing the acquisition of these seeds is crucial for developing effective support strategies for local farmers. This study aimed to analyze the factors affecting the acquisition of improved corn seeds in three communities within the municipality of Paso de Ovejas, Veracruz, Mexico. A survey method and semi-structured interviews were conducted with 103 producers. Agricultural technicians and neighboring farmers were identified as the primary sources of information on seed use. Economic and social factors were found to have the greatest influence on access to information. Hybrid seeds from transnational companies, such as Monsanto and Pioneer, dominated the market, accounting for 83% of seed purchases. These seeds were more expensive than those from national companies, with an average cost of $5,728 per producer. Economic factors were determined to be the most significant influence on the purchase of improved seeds, outweighing social, political, and human factors.